Progressive Suppleness Pursil Catheter: a new tool for superselective angiography and embolization. - Dion, J E; Duckwiler, G R; Lylyk, P; Viñuela, F; Bentson, J (American Journal of Neuroradiology, 1989)
300 Multiple ChoicesThis is a pdf-only article and there is no markup to show you.full-text.pdf